Effects of attitude and destination image on association members’ meeting participation intentions: development of meeting participation model - Lee, Myong Jae (Kansas State University, 2005)
Understanding association members’ meeting participation behaviors is the key to the well-attended meeting, which is a common goal of both associations and host destinations. However, little research has contributed to theoretical development in this area, and the lack of a theoretical framework has negatively influenced the validity of existing research. Thus, this study attempted to explain association members’ meeting participation behaviors, using a conceptually sound model of meeting participation, which was developed based on existing human behavior theories: the theory of reasoned action (TRA) and the theory of planned behavior (TPB). Another main objective of this study was to test the validity of the meeting participation model (MPM). By comparing the utility of three competing models (TRA, TPB, and MPM), this study confirmed the effectiveness of the meeting participation model (MPM) in explaining association members’ intentions to attend the annual meeting. The proposed meeting participation model was empirically examined using the data collected from 245 members of the International Council on Hotel, Restaurant, and Institutional Education (CHRIE). The results of model development revealed that the MPM fits the data very well, providing a systematic view of the decision-making process of association meeting participation. In addition, the findings of the model comparison using the structural equation modeling (SEM) revealed that all three competing models successfully provide a theoretical base for understanding association members’ meeting participation behaviors. Specifically, the MPM provided a fuller understanding of meeting participation intention by adding two predictor variables (destination image and past meeting participation experience) to the TPB. This study is the first research effort to investigate what makes association members attend, or not attend, association meetings based on theoretical frameworks. TRA and TPB provided the necessary theoretical ground to develop the meeting participation model (MPM). By adding a domain specific predictor variable (destination image) and a non-volitional habitual construct (past experience) to the original latent constructs conceptualized in pure TRA/TPB models, the MPM emerged as a theoretically strong and parsimonious framework for understanding association members’ meeting participation behaviors. The results of the current study present a strong step toward providing practical as well as theoretical implications for future convention research.
Keywords: Association meeting; Theory of planned behavior; Theory of reasoned action; Destination image; Meeting participation model; Sociology, General (0626)